Student’s Achievement of Learning Competencies and Challenges in Learning World History in Public High Schools - Delaben, Rudylyn P.; Bual, Joel M. (Philippine Social Science Journal, 2025)
This quantitative study assessed World History achievement and learning challenges among 269 Grade 8 students in Northern Negros Occidental public schools during the 2023–2024 academic year. Using stratified random sampling and validated instruments, the research found that while students generally demonstrated a proficient level of achievement, significant performance differences existed relative to sex and parents’ educational attainment. Key challenges identified included students’ difficulties with reading and memorization, instructional gaps such as a lack of feedback and real-world connections, and inadequate resources in both school and home environments. To address these barriers and elevate student mastery, the study proposes a Strategic Intervention Material (SIM), while recommending that future research expand the scope to larger demographics and additional curricular quarters to further enhance instructional quality.